Kajian Fasad Bangunan terhadap Visual Connection di Koridor Jalan Teuku Umar, Denpasar - Gamana Pratama, A. A. Gede Trisna (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2019)
The development and growth of Denpasar City is accompanied by the development of diverse architecture. Mainly at Teuku Umar streetas one of the commercial centers there. It will affect the image of a city if the building façade doesn’t directed according to how the government wants based on regional Regulation Number 27 of 2011 about Denpasar city layout project. This research uses descriptive qualitative research with rationalistic approach based on the facts at the field, with primary data observations and direct documentation of building facade. The results of this research indicate visual connection which formed in this corridor is dominated by commercial buildings, so it contributes the modern building architectural image which is dominated.This kind of thing is still outlyingfrom what was expected from the look of Denpasar city. Whereas Denpasar should be a cultural insightful city although Teuku Umar street is one of the commercial and services center in Denpasar city. Denpasar government who take the responsibility of the wisdom is expected to make the reference of using building façade more specific based on the function of the building itself and not to generalize them. So as the function of commercial calibrate the look of the building that can attract the interest of customers and also can appropriate to how Denpasar city wants the city look like. Keywords: building facade, visual connection, Teuku Umar street corridor Denpasar (Times New Roman 10t, Blank, Times New Roman 12pt, Single-before 0-after 6) Abstrak ( Times New Roman 12pt, Bold, Multiple at 1.15-before 0-after 6) Perkembangan dan pertumbuhan Kota Denpasar diiringi dengan perkembangan arsitektur yang beragam.Terutama di koridor Jalan Teuku Umar sebagai salah satu pusat komersial di Kota Denpasar. Hal tersebut mempengaruhi image sebuah koridor kota melalui tampilan fasad bangunan yang ada, tidak diarahkan sesuai wajah kota yang dinginkan pemerintah berdasarkan Peraturan Daerah No 27 Tahun 2011 tentang Rencana Tata Ruang Wilayah Kota Denpasar. Penelitian ini menggunakan penelitian kualitatif deskriptif dengan pendekatan rasionalistik berdasarkan kenyataan dilapangan, dengan data primer diperoleh dari hasil observasi, dokumentasi langsung berupa image fasad bangunan. Hasil penelitian menunjukkan visual connection yang terbentuk pada koridor ini didominasi bangunan komersial, sehingga memberikan image bangunan arsitektur modern yang mendominasi tampilan fasad bangunan. Hal ini masih sangat jauh dari apa yang diharapkan dari wajah kota Denpasar yang berwawasan budaya, namun dengan kondisi Koridor Jalan Teuku Umar yang merupakan salah satu pusat perdagangan dan jasa di Kota Denpasar. Diharapkan pada pengampu kebijakan yakni Pemerintah Kota Denpasar agar membuat acuan mengenai penggunaan fasad bangunan lebih khusus berdasarkan jenis fungsi bangunan dan tidak mengeneralisir sehingga pada fungsi bangunan komersial dapat menyesuaikan tampilan yang dapat menarik minat pengunjung dan juga sesuai dengan wajah kota yang diinginkan Kota Denpasar. Kata kunci: fasad bangunan, visual connection , Koridor Jalan Teuku Umar Denpasar